The Development of Mindful-Based Dance Movement Therapy Intervention for Chronic Pain: A Pilot Study With Chronic Headache Patients - Majore-Dusele, Indra; Karkou, Vicky; Millere, Inga (Frontiers in Psychology, 2021)
Chronic pain is of significant global concern. There is growing evidence that body-mind therapies and psychological approaches can contribute towards changing chronic pain perceptions. This is the first model described in the literature that combines a mindfulness-based approach with dance movement therapy, and explores potential psychological and pain-related changes for this client population. In this paper results from the pilot study are presented involving patients with chronic headache recruited in an outpatient rehabilitation setting. Methods: In this pilot study 29 patients (n=29) with chronic headache were randomized to either an MBDMT group or a waiting list control group (TAU). The MBDMT group was offered ten sessions in a clinical outpatient rehabilitation setting for five weeks. Data were collected pre- and post-intervention and 16 weeks after the intervention finished. The Hospital Anxiety and Depression scale (HADS), Patient Health questionnaire (PHQ-9), Five Facets of Mindfulness questionnaire (FFMQ) and Numeric Pain rating scale (NRS) were used as outcome measures. Results: The working model of MBDMT identifies nine therapeutic mechanisms (safe therapeutic environment, mindfulness skills, body awareness, relaxation / releasing, distancing and staying with discomfort, meaning making, self-regulation, acceptance and integration, creative process). Per-protocol analysis reveals statistically significant reduction of pain intensity and depression scores in favor of the MBDMT group and these improvements were maintained in follow-up assessment. Conclusions: Results suggest that MBDMT is a feasible and promising therapy approach for chronic pain patients. The pilot study offered sufficient information and preliminary results in the desirable direction to enable the researchers to move to an RCT stage in order to establish the efficacy of the intervention. Trial registration: the study was registered in the www.researchregistry.com registry (5483).